Bridging the Gap: The Urgent Need for Integrated Microplastic and Human Health Research in Indonesia - Novirsa, Randy; Ilmaskal, Radian; Daswito, Rinaldi (Journal of Health Sciences and Epidemiology, 2025)
Microplastic pollution poses a critical global public health challenge, with Indonesia as a major contributor. While ecological impacts are studied, direct human health effects remain underexplored locally. Evidence shows widespread microplastic contamination in essential resources, leading to human exposure and potential health risks like oxidative stress and endocrine disruption. Current Indonesian research is fragmented, lacking standardized methodologies and comprehensive health risk assessments. An integrated EcoHealth approach, combining environmental monitoring with clinical toxicology and public health frameworks, is imperative. Establishing standardized protocols and probabilistic risk models is crucial for effective policy development and safeguarding Indonesia's public health and blue economy.